The birth of insight : meditation, modern Buddhism, and the Burmese monk Ledi Sayadaw - Braun, Erik, 1972- (Buddhism and modernity., 2013)
Insight meditation, which claims to offer practitioners a chance to escape all suffering by perceiving the true nature of reality, is one of the most popular forms of meditation today. The Theravada Buddhist cultures of South and Southeast Asia often see it as the Buddha's most important gift to humanity. In the first book to examine how this practice came to play such a dominant-and relatively recent-role in Buddhism, Erik Braun takes readers to Burma, revealing that Burmese Buddhists in the colonial period were pioneers in making insight meditation indispensable to modern Buddhism. </DI.